(untitled) (Iranian Journal of Kidney Diseases, 2009)
Benign multilocular cyst is a rare benign multicystic renal tumor. It usually involves the kidneys unilaterally. There is no generally accepted theory concerning its pathogenesis. The usual clinical presentation is an asymptomatic abdominal mass in children and nonspecific symptoms such as abdominal pain, hematuria, and urinary tract infection in adults. This report presents a case of benign multilocular cyst in an 18-months-old boy admitted with abdominal distension and a palpable mass in his right loin. The patient underwent right total nephrectomy, and histological findings were compatible with benign multilocular cyst.